A New Universal Simplified Adhesive: 6‐Month Clinical Evaluation. Issue 1 (15th November 2012) - Mena‐Serrano, Alexandra; Kose, Carlos; De Paula, Eloisa Andrade; Tay, Lidia Yileng; Reis, Alessandra; Loguercio, Alessandro D.; Perdigão, Jorge
<x xml:space="preserve">Abstract</x> Statement of the Problem Multimode adhesives, which can be used as etch‐and‐rinse or as self‐etch adhesives, have been recently introduced without clinical data to back their use. Purpose of the Study To evaluate the 6‐month clinical performance of Scotchbond Universal Adhesive (SU; 3M ESPE, St. Paul, MN, USA) in noncarious cervical lesions (NCCLs) using two evaluation criteria. Methods/Materials Thirty‐nine patients participated in this study. Two hundred restorations were assigned to four groups: SU‐TEm: etch‐and‐rinse + moist dentin; SU‐TEd: etch‐and‐rinse + dry dentin; SU‐SEet: selective enamel etching; and SU‐SE: self‐etch. The composite resin Filtek Supreme Ultra (3M ESPE) was placed incrementally. The restorations were evaluated at baseline and after 6 months using both the World Dental Federation (FDI) and the United States Public Health Service (USPHS) criteria. Statistical analyses were performed with Friedman repeated measures analysis of variance by rank and McNemar test for significance in each pair (α = 0.05). Results Only four restorations (SU‐SE: 3 and SU‐TEm: 1) were lost after 6 months (p > 0.05 for either criteria). Marginal discoloration occurred in one restoration in the SU‐SE group (p > 0.05 for either criteria). Only 2/200 restorations were scored as bravo for marginal adaptation using the USPHS criteria (one for SU‐SE and one for SU‐SEet, p > 0.05). However, when using the FDI criteria, the percentage of bravo scores for marginal adaptation at 6 months were 32%, 36%, 42%, and 46% for groups SU‐TEm, SU‐TEd, SU‐SEet, and SU‐SE, respectively (p > 0.05). Conclusions The clinical behavior of the multimode adhesive does not depend on the bonding strategy at 6 months. The FDI evaluation criteria are more sensitive than the USPHS criteria. Clinical Significance At 6 months, the clinical behavior of the new multimode adhesive Scotchbond Universal was found to be reliable when used in noncarious cervical lesions and may not depend on the bonding strategy employed.